Study of compacted soil layers in the out-season soybean corn agricultural system in the Araguaia-Xingu Region - Macena, P. H. C.; Castro, Y. O.; Neto, D. C. O. Riva; Marinho, N. F.; Sant’anna, J. A. V. (Scientific Electronic Archives, 2021)
Resistance to Penetration (RP) can be found on various soil conditions and even on different agricultural production systems. The present work aimed to diagnose compacted layers along the soil profile. For the development of the work, it was necessary to use a specific equipment for data collection of RP whose name and Digital Penetrometer (Falker). Able to measure compacted layers every 5 cm depth up to a distance of 60 cm. along the soil profile in addition, it is able to provide data via graphs through a computer system. Random collections were carried out on different farms in the Araguaia Xingu region, so the criterion used to develop the work was to collect 15 points per plots at a maximum depth of 40cm and the same should be found in its third year of soybean cultivation. Corn (Safrinha). A total of 135 points were collected along 9 farms in the region, and after analyzing the points through the PenetroLOG Software. An average of the 15 points of each farm was carried out, as well as the final average of all the farms to reinforce the individual means. It was concluded that, in the soybean and maize out-season system, the compacted layer is between 14 and 20 cm deep along the soil profile with mean values of pressure of 1975 and 2504 kpa. This suggests alteration of the management used in the soils of the evaluated areas.